KAJIAN MAKNA PANTANG LARANG PADA MASYARAKAT BUGIS DI DESA SUNGAI SEBESI KECAMATAN KUNDUR - Sandi, Jibril Pratama Artha; Shanty, Isnaini Leo; Leoni, Tessa Dwi; Malik, Abdul; Irawan, Dody; Zaitun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the connotative meanings of Bugis taboo expressions (pantang larang) in Sungai Sebesi Village, Kundur District, Karimun Regency. The research was motivated by the gradual decline in public understanding, particularly among the younger generation, of the cultural meanings embedded in these traditional expressions despite their continued use in daily life. The study aimed to analyze the connotative meanings contained in Bugis taboo expressions using a semantic approach. A qualitative descriptive method was employed. Data were collected through observation, in-depth interviews, and documentation involving community members who possess knowledge of the tradition. The collected data were analyzed through data reduction, data presentation, and conclusion drawing. The findings revealed 26 Bugis taboo expressions that remain preserved within the community. All identified expressions convey positive connotative meanings, reflecting moral values, politeness, discipline, responsibility, respect for parents and elders, appreciation for sustenance, social harmony, and local wisdom. Rather than functioning solely as prohibitions rooted in traditional beliefs, these taboo expressions serve as oral cultural media for transmitting ethical values and regulating social behavior across generations. This study contributes to semantic and folklore studies by documenting the cultural meanings embedded in Bugis taboo expressions and highlighting their continuing relevance as a form of local wisdom in contemporary society.